Beyond the Blood:Brain Barrier: The Importance of Central Nervous System (CNS) Pharmacokinetics for the Treatment of CNS Tumors, Including Diffuse Intrinsic Pontine Glioma - Warren, Katherine Elizabeth (Frontiers in Oncology, 2018)
Over the past decade, we have made considerable progress in establishing diffuse intrinsic pontine glioma (DIPG) as a disease entity and developing pre-clinical tools to interrogate potential therapeutics. However, translation to improved clinical outcomes in children with DIPG have not yet been realized. This is in part due to difficulties encountered in delivering active drugs adequately to the tumor site. However, most pre-clinical evaluations gloss over the fundamental concepts of CNS pharmacokinetics and requirements needed to optimize drug delivery and exposure and translate this into efficacious therapy. This article discusses not only the blood:brain barriers, but additional barriers to drug delivery for CNS tumors and pharmacokinetic principles that need to be addressed and considered.